(3QjGV GdWGdHjfs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg GdEYGfg hGdJjSjQ gPG JYdjb dWja Ydi GdESJYGPI hGdHSedI hSejJg QjGV GdWGdHjf hajg SHYI CHhHG hNGJeI GdHSedI ai CUdgG s
(3BNQgG (B:s
(3acGf EPG hVYgG Ydi QCSg Scf UOGYg hEPG QaYgG YGO GdUOGY aaJMgG aEPG ajgG cGZO ajg HSe Gddg GdQMef GdQMje hgPG BNQ eG JjSQ ef GdJYdjb hGddg hdi GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdeLGejYs